Ochrona interesów pokrzywdzonego (osoby fizycznej) w świetle przepisów polskiego prawa karnego materialnego oraz działalności państwa na rzecz ofiar przestepstw: [The protection of interests of the person injured by the offence (natural person) by substantive law and the state in Poland] (Studia Prawnicze / The Legal Studies, 1985)
The article attempts to analyze binding legal regulations from the point of view of the protection of interests of persons injured by the offence, especially those which so far have been seldom considerd from this point of view. The author points out to the fact that in Poland the trend has been developed which focussed on the victim of the offence (natural person) which in the world literature is referred to as the so-called procedural victimology. The Supreme Court's guiding principles for the judiciary on strengthening the protection of interests of injured persons in criminal cases, as well as the changes, in the 80's in the code of criminal procedure, are also connected with that trend.However, it has been pointed that the situation of the injured person does not merely depend on regulations by law of criminal proceedings but also by substantial criminal law and on the assistance rendered to the injured person by the state and society in the realization of his rights and duties.In the sphere of substantive criminal law, the following articles are especially important for the protection of interests of injured persons: art. 50 § 2 of the penal .code, art. 57 § 2 item 1 of the penal code and r provision's Providing for joint penal measures with the possibility to impose certain obligations on the perpetrator in order to satisfy the 'interests of the injured person. The author points to two obligations of this kind in the penal code, namely an obligation to redress in whole or in part the damage caused by the offence and to apologize to the injured person. It is possible to impose them together with ruling on conditional discontinuance of criminal proceedings (art. 28 § 2, 1 and 2 of the penal code), the penalty of limitation of liberty (art. 35 of the penal code) suspending the execution of a penalty (art. 75 § 2, item 1 and 2) and conditional release (art. 94 of the penal code). However, it has been revealed that these obligations have been rarely imposed in practice.Moreover, the institution of smart mony was also discussed. the imposition of which gives rise to serious doubts and reservations. The provision of art. 49 of the penal code, stating that the court may order the publication of the sentence for public information has been also mentioned, as well as the provision of art. 180 of the penal code which concerns a very similar case.As far as the state assistance to the injurred person is concerned, it has been observed that the issue has not been so far dealt with, although there were two suggestions on establishing a fund for victims of offences, and, moreover, injured persona and their families may be granted material assistance from the so-called postpenitentiary assistance fund.It has also been stressed that, first of all, the problem should be considered what categories of victims cannot actually be granted assistance from either of the funds and their needs should be first of all taken into consideration.In general, it has been said that injured persons should be considered in the process of shaping and applying ,norms of penal law and in the activities of the state and its organs.